IMPLEMENTASI EVOLUTIONARY PROTOTYPING PADA SISTEM INFORMASI PENGELOLAAN PENELITIAN DAN PUBLIKASI ONLINE DI LEMBAGA PENELITIAN UNIVERSITAS LANGLANGBUANA - Awan Setiawan (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
This research aims to implement an online research and publication management information system at the Langlangbuana University Research Institute. In the digital era, research institutions need an economically efficient system to facilitate research and publication management and increase the accessibility of research information. The research uses Evolutionary Prototyping for system development. This allows responsiveness to changing user needs. The implementation stage includes identifying the need for research management and online publications. It is hoped that the results of this research will serve as a guide for a better system, increase efficiency, facilitate publication, and increase the visibility of research results. With a good information system, the Langlangbuana University Research Institute can strengthen its position, increase collaboration, and provide greater benefits for the public and other users who are interested in the research results